Interpreting probability models logit, probit and other generalized linear models - Liao, Tim Futing (Thousand Oaks, [Calif.] ; London : SAGE, 1994)
What is the probability that something will occur, and how is that probability altered by a change in an independent variable? To answer these questions, Tim Futing Liao introduces a systematic way of interpreting commonly used probability models.
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Linear models (Statistics); Logits; Probits